2023
DOI: 10.3390/molecules28052048
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from the Roots of Sophora flavescens and Their Potential Anti-Inflammatory and Antiproliferative Activities

Abstract: The phytochemical investigation of the roots of the traditional Chinese medicinal plant Sophora flavescens led to the isolation of two novel prenylflavonoids with an unusual cyclohexyl substituent instead of the common aromatic ring B, named 4′,4′-dimethoxy-sophvein (17) and sophvein-4′-one (18), and 34 known compounds (1–16, 19–36). The structures of these chemical compounds were determined by spectroscopic techniques, including 1D-, 2D-NMR, and HRESIMS data. Furthermore, evaluations of nitric oxide (NO) prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…These substances are highly unstable and possess potent oxidizing properties, and they dissolve in water in large quantities during exposure to plasma, resulting in an elevation of EC [6]. Yang et al [4] investigated the EC variation in PAWs; they revealed a drastic increase in EC within a 5-minute timeframe. This notable increase was primarily attributed to the generation of active substances, such as ROS and RNS, which are formed when air is ionized and dissolved in water.…”
Section: Temperature Ec and Phmentioning
confidence: 99%
See 2 more Smart Citations
“…These substances are highly unstable and possess potent oxidizing properties, and they dissolve in water in large quantities during exposure to plasma, resulting in an elevation of EC [6]. Yang et al [4] investigated the EC variation in PAWs; they revealed a drastic increase in EC within a 5-minute timeframe. This notable increase was primarily attributed to the generation of active substances, such as ROS and RNS, which are formed when air is ionized and dissolved in water.…”
Section: Temperature Ec and Phmentioning
confidence: 99%
“…Yang et al [4] noticed that the pH of the PAW dropped as the treatment duration increased. This pH decrease was a result of water ionization, resulting in the generation of H+ ions and acidic compounds such as nitric acid and nitrous acid.…”
Section: Temperature Ec and Phmentioning
confidence: 99%
See 1 more Smart Citation
“…The main edible part of asparagus is the spear, which is delicious and rich in nutrients such as various types of amino acids, minerals, and phytochemicals such as steroids, flavonoids, and other bioactive ingredients (Fuentes‐Alventosa et al., 2009 ; Yi et al., 2019 ). Flavonoids are important components in asparagus, which may provide antiallergic, anti‐inflammatory, antiviral, and antioxidant activities to human body (Ferreyra et al., 2012 ; Franca et al., 2023 ; Li et al., 2023 ; Silva et al., 2023 ; Xu et al., 2023 ; Yang et al., 2023 ; Zhang et al., 2023 ). Rutin comprises the largest proportion of flavonoids in asparagus (Fuentes‐Alventosa et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are important components in asparagus, which may provide antiallergic, anti-inflammatory, antiviral, and antioxidant activities to human body (Ferreyra et al, 2012;Franca et al, 2023;Silva et al, 2023;Xu et al, 2023;Yang et al, 2023;Zhang et al, 2023). Rutin comprises the largest proportion of flavonoids in asparagus (Fuentes-Alventosa et al, 2007).…”
mentioning
confidence: 99%